(untitled) (Journal of Parents and Teachers, 2013)
Currently there are plenty of variety and offer of after school activities which reduce the playing time in favour of their intellectual development. Therefore we forget that playing also means developing cognitive and psychomotor skills, creativity and socialization. Every toy has an educational function if we take advantage of the positive characteristics it has including the so considered gender based characteristics, given by adults, not kids. It is recommendable to let the kid choose to help him develop their personality. This problem comes straight from advertising and although supervising institutions are created on that purpose, it is necessary to explain kids what they see on tv. It is the same situation with videogames, as these are not always negative for them, but they can also contribute in a good way to the kids’ development and learning.